Sales Team Performance Improvement Strategy in Increasing Sales Volume: Case Study at Medan Yamaha Center - Nainggolan, Agustina; Aprinawati, Aprinawati; Manik, Enjelia; Sinaga, Mulyati Patresia; Kabeakan, Siat Putri (Economic: Journal Economic and Business, 2025)
This study analyzes the effect of teamwork on employee performance at Kemang Jaya 2 Restaurant using a qualitative approach. The results of the study indicate that effective teamwork, supported by good communication and inclusive leadership, has a positive impact on increasing employee productivity and job satisfaction. However, challenges such as work discipline and interpersonal conflict are still obstacles that need to be managed strategically. The recommendations of this study include communication training, conflict management, and collaborative skills development to create a more conducive work environment. With this strategy, it is hoped that organizations can improve operational effectiveness and competitiveness in the competitive restaurant industry.